Glass roofs of courtyards: too much care breaks the glass? (Bulletin KNOB, 2008)
The phenomenon of (glass) roofs of courtyards of listed buildings during the past three decades became the subject of a research with respect to Dutch heritage. An inventory was made of 25 objects. In chronological order ten listed buildings are brought up which stirred up the most interesting discussion. The role of the RACM is central to the appraisal of plans and recommendations concerning the addition of a new modern layer to an existing and acknowledged listed building. In the course of nearly 30 years a trend is apparent in the advice given, moving from an ‘in principle no’ by way of a policy of ‘tolerance’ to a ‘proactive yes’.This evolution resulted in presentation of new policy by the of RACM department in 2007, stating that more than ever before citizens will be welcome in the domain of cultural heritage. The research also showed that the greater part of the glass roofs are applied for because of an improved ambience and provision of services to the public. Furthermore, it continues to be of importance that the new facility is transparent and designed in an architecturally modern way. The technical requirements of reversibility and good maintenance should also be retained. The eventual result may then signify an added value for the combination.